WORKSHOP PEDAGOGICAL KNOWLEDGE GURU MUHAMMADIYAH KABUPATEN BUNGO UNTUK MENINGKATKAN KETERAMPILAN ABAD 21 - Pitra, Dedek Helida; Wiyoko, Tri; Habibie , Zulqoidi R. (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2025)
21st century skills, such as critical thinking, creativity, collaboration, and communication, are the main demands in the modern world of education. However, Muhammadiyah teachers in Bungo Regency still face the challenges of the times in implementing learning approaches that support mastery of these skills. Observation results show that most teachers have limitations in mastering Pedagogical Knowledge (PK) and integrating technology into learning. Community service activities aim to improve teachers' understanding and skills in implementing Pedagogical Content Knowledge (PCK) and Technological Pedagogical Content Knowledge (TPACK) through intensive Workshop-based training. The method used in this community service activity applies the Community-Based Education approach, which involves teachers as active partners in the training process. This activity includes three main stages: situation analysis to identify teacher needs, implementation of practice-based workshops, and evaluation of the impact of training on improving teacher pedagogical competence. The workshop includes materials on Higher Order Thinking Skills (HOTS), project-based learning strategies (Project-Based Learning), and the use of technology in teaching. The evaluation results showed a significant increase in participants' understanding of the PK and TPACK concepts, as well as an increase in their skills in designing and implementing innovative learning methods. In addition, a teacher learning community was formed that supports reflection and continuous improvement of competencies. Thus, this community service activity provides solutions to the problems faced by partners and contributes to improving the quality of education in Muhammadiyah schools in Bungo Regency and invited participants who attended the workshop activities that have been implemented.